A DEMONSTRATIVE-KINESTHETIC TEACHING APPROACH FOR INVERSE KINEMATICS OF A 4-DOF ROBOT MANIPULATOR - Mabong, Griffin P.; Osore, Emmanuel A. E.; Cherop, Peter T. (Journal of Applied Engineering Science, 2024)
Kinesthetic guidance as a paradigm of programming by demonstration of robot manipulators has eased the process of robot programming, especially for non-skilled and semi-skilled shop-floor operators in manufacturing industries. Today, the inverse problem remains an area of interest in robotics, leading up to the deployment of robots for collaborative technology with humans. The paper proposes using a demonstrative-kinesthetic teaching technique to program a robot manipulator, determine the inverse kinematics using the approach, and compare with structured texts to program the manipulator. The approach was carried out on a Dobot magician, a 4-DOF robot manipulator. A control platform was created using MS Visual Studio IDE, using Python to control the arm, and it was programmed demonstratively using the lock arm button and structured texts to carry out a palletizing task. The joint parameters were collected and compared using the demonstrative-kinesthetic technique and structured texts as programming methods. The structured texts were used as a control for the experiment. The results showed that joint values obtained using the demonstrative-kinesthetic technique did not vary significantly from structured texts’ joint values. The approach provided an avenue for quickly programming a robot manipulator, especially concerning the non-skilled workforce, and finding analytical solutions to the inverse problem of the robot manipulator.